2022
DOI: 10.13057/biodiv/d230608
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis pattern and antibiotic susceptibility testing in female patients using high vaginal swabs

Abstract: Abstract. Al-Kraety IAA, Al-Muhanna SG, Banoon SR, Ghasemian A. 2022. Bacterial vaginosis pattern and antibiotic susceptibility testing in female patients using high vaginal swabs. Biodiversitas 23: 2838-2844. Bacterial species found in the vaginal environment encompass a wide variety of species. A common cause of vaginal discharge in women is bacterial vaginosis BV (BV). Various Gram-positive and Gram-negative rod shaped bacteria, including E. coli, Klebsiella spp., Enterococcus spp., Enterobacter spp., Raoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…(17.3%), and Staphylococcus spp. (17.3%) were the most common isolates [ 6 ]. Another study showed that the most prevalent pathogen was E. coli , Klebsiella pneumoniae , Staphylococcus aureus , and Citrobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(17.3%), and Staphylococcus spp. (17.3%) were the most common isolates [ 6 ]. Another study showed that the most prevalent pathogen was E. coli , Klebsiella pneumoniae , Staphylococcus aureus , and Citrobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies reported that Klebsiella spp. exhibited high resistance to ampicillin and trimethoprim-sulfamethoxazole [ 6 ] and isolates exhibited high resistance (>60%) to nitrofurantoin, cephalexin, ceftazidime, and ceftriaxone [ 21 ]. This could be mainly due to the fact that these antibiotics are among the antibiotics commonly prescribed for these gram-negative bacteria for different diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations